FORUM MŁODYCH CHIRURGÓWEmergency redo coronary bypass surgery with application of both radial arteries and small saphenous vein in a 55-year-old male. Case report - Rachwalik, Maciej; Lipińska, Małgorzata; Bielicki, Grzegorz; Nowicki, Rafał; Pelczar, Marek; Goździk, Waldemar; Kustrzycki, Wojciech (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2009)
Myocardial infarction as an early complication after CABG contributes to higher postoperative mortality. Redo CABG is connected with higher risk than first time CABG. Choice of the conduit during redo surgery is influential for postoperative follow-up. Radial arteries are relatively infrequently applied during redo emergency surgery. One of the factors influencing the results of redo CABG is myocardial protection. Retrograde administration of cardioplegia (RCP) resuscitates the ischaemic myocardium and gives good myocardial preservation. We present a case of emergent redo coronary surgery with the application of radial arteries.